Bibliometric analysis of international scientific production on salivary biomarkers during the period 2004-2018 (Revista Nacional de Odontología, 2020)
Introduction: saliva protects the integrity of oral tissues, but also offers evidence of local and systemic diseases. Bibliometry in studies related to dentistry is uncommon in the literature. From this perspective, the objective of this study was to map the scientific landscape related to the research of salivary biomarkers around the world between 2004 and 2018.Methods: This study adopted a bibliometric method. A documentary, observational, descriptive, retrospective research was conducted, with quantitative description of the data. Dentistry & Oral Sciences Source has been selected as an online bibliometric database to search and retrieve documents. All data presented in this study were analyzed using the following software programs: VOSviewer, Publish or Perish, Mendeley Desktop and SPSS version 19 for Windows. Descriptive and inferential statistical methods were used.Results: 218 documents were registered. The means and standard deviation of the publications between 2004-2011 (4.67 ± 1.52) and 2012-2018 (24.67 ± 2.47) showed significant differences (p = 0.001). Periodontal disease (37%) and oral cancer (20%) were the most studied diagnostic subjects. Wong DT (University of California, Los Angeles, USA) was the author with the most articles (5.96%).Conclusion: during the study period, international research on salivary biomarkers was increased, indicating the importance of salivary components for novel approaches to prognosis, diagnosis and monitoring of patients with oral and systemic diseases.
Keywords: saliva; biomarkers; bibliometrics; publications